Estimation of effective properties of composite sandwich panels with negative Poisson's ratio by using variational asymptotic multiscale method. (June 2020) - Xiao, Peng; Yifeng, Zhong; Zheng, Shi; Peng, Wang
Highlights: The multiscale effective properties of composite sandwich panel are well predicted. Compared with 3D FEM, VAMM has much lower calculation cost and comparable accuracy. The influence of layup configuration and fiber volume fraction are intensive studied. The negative Poissons ratio (NPR) is greatest with special orthogonal layup configuration. The degree of anisotropy and NPR decrease with the increase of fiber volume fraction. Abstract: According to the anisotropy and non-homogeneity of composite sandwich panels with negative Poisson's ratio (NPR), the variational asymptotic method combined with multiscale technology (VAMM) is used to analyze its effective properties. Firstly, in the microscale, the effective properties of the unidirectional fiber reinforced composite (UDFRC) forming the facesheets are obtained by means of asymptotic homogenization analysis, which can be used as lamina properties. Then, in the mesoscale, an asymptotic analysis of the typical unit cell is carried out to deduce the effective plate properties ( A, B, and D matrices) of composite sandwich panels with NPR according to the heterogeneity of the structure. Finally, the influence of the layup configurations and fiber volume fractions of UDFRC on the equivalent plate properties of composite sandwich panels with NPR is analyzed. Numerical results show that the 3D responses of composite sandwich panels with NPR using VAMM are in agreement with those of 3D FEM model, while in a much more efficient manner. The layup configurations of facesheets have great influence on the equivalent plate properties of the structure. Furthermore, the degree of anisotropy and negative Poisson's ratio of the whole structure decrease with increasing fiber volume fraction of UDFRC.